Groove pancreatitis – an unusual case of pancreatitis, case report - Ślósarz, Tymoteusz; Walęcik-Kot, Weronika; Kaczorowski, Rafał (Quality in Sport, 2024)
Groove pancreatitis is a rare form of chronic pancreatitis affecting the pancreaticoduodenal groove, leading to ductal stenosis and symptoms like abdominal pain, vomiting, and jaundice. It often coexists with cystic dystrophy of the duodenal wall (CDDW), marked by duodenal wall thickening and cyst formation. We report a case of a 36-year-old male with persistent abdominal pain and a history of acute pancreatitis, diagnosed with CDDW via MRI. Despite multiple endoscopic interventions, ductal access was challenging due to inflammation and conservative management with proton pump inhibitors and pancreatic enzymes provided symptom relief. Diagnostic tools include MRI, endoscopy, and EUS were administered. Management of groove pancreatitis still remains a challenge consisting of treatment ranging from conservative methods to surgical intervention for refractory cases, emphasizing a cautious, stepwise approach and lifestyle changes.